Difference between revisions of "009A Sample Midterm 2, Problem 3"

From Math Wiki
Jump to navigation Jump to search
Line 1: Line 1:
 
<span class="exam">Use the definition of the derivative to find &nbsp; <math>\frac{dy}{dx}</math> &nbsp; for the function &nbsp;<math style="vertical-align: -12px">y=\frac{1+x}{3x}.</math>
 
<span class="exam">Use the definition of the derivative to find &nbsp; <math>\frac{dy}{dx}</math> &nbsp; for the function &nbsp;<math style="vertical-align: -12px">y=\frac{1+x}{3x}.</math>
 +
<hr>
  
 +
[[009A Sample Midterm 2, Problem 3 Detailed Solution|'''<u>Detailed Solution with Background Information</u>''']]
  
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
+
[[File:9ASM2P3.jpg|600px|thumb|center]]
!Foundations: &nbsp;
 
|-
 
|Recall
 
|-
 
|&nbsp; &nbsp; &nbsp; &nbsp;<math style="vertical-align: -13px">f'(x)=\lim_{h\rightarrow 0}\frac{f(x+h)-f(x)}{h}</math>
 
|}
 
  
 
'''Solution:'''
 
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Step 1: &nbsp;
 
|-
 
|Let &nbsp;<math style="vertical-align: -14px">f(x)=\frac{1+x}{3x}.</math>
 
|-
 
|Using the limit definition of derivative, we have
 
|-
 
|&nbsp; &nbsp; &nbsp; &nbsp; <math>\begin{array}{rcl}
 
\displaystyle{f'(x)} & = & \displaystyle{\lim_{h\rightarrow 0} \frac{f(x+h)-f(x)}{h}}\\
 
&&\\
 
& = & \displaystyle{\lim_{h\rightarrow 0} \frac{(\frac{1+(x+h)}{3(x+h)})-(\frac{1+x}{3x})}{h}}\\
 
&&\\
 
& = & \displaystyle{\lim_{h\rightarrow 0} \frac{(\frac{1+x+h}{3x+3h})-(\frac{1+x}{h})}{h}.}
 
\end{array}</math>
 
|}
 
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Step 2: &nbsp;
 
|-
 
|Now, we get a common denominator for the fractions in the numerator.
 
|-
 
|Hence, we have
 
|-
 
|&nbsp; &nbsp; &nbsp; &nbsp; <math>\begin{array}{rcl}
 
\displaystyle{f'(x)} & = & \displaystyle{\lim_{h\rightarrow 0}\frac{\frac{(1+x+h)3x}{(3x+3h)(3x)}-\frac{(1+x)(3x+3h)}{(3x+3h)(3x)}}{h}}\\
 
&&\\
 
& = & \displaystyle{\lim_{h\rightarrow 0}\frac{\frac{3x+3x^2+3xh-(3x+3h+3x^2+3hx)}{(3x+3h)(3x)}}{h}}\\
 
&&\\
 
& = & \displaystyle{\lim_{h\rightarrow 0} \frac{-3h}{h(3x+3h)(3x)}}\\
 
&&\\
 
& = & \displaystyle{\lim_{h\rightarrow 0} \frac{-3}{(3x+3h)(3x)}}\\
 
&&\\
 
& = & \displaystyle{\frac{-3}{(3x)(3x)}}\\
 
& = & \displaystyle{-\frac{1}{3x^2}.}
 
\end{array}</math>
 
|}
 
 
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Final Answer: &nbsp;
 
|-
 
|&nbsp; &nbsp; &nbsp; &nbsp; <math>\frac{dy}{dx}=-\frac{1}{3x^2}</math>
 
|-
 
|
 
|}
 
 
[[009A_Sample_Midterm_2|'''<u>Return to Sample Exam</u>''']]
 
[[009A_Sample_Midterm_2|'''<u>Return to Sample Exam</u>''']]

Revision as of 09:08, 7 November 2017

Use the definition of the derivative to find     for the function  


Detailed Solution with Background Information

9ASM2P3.jpg

Return to Sample Exam